Application of Pancasila Values to Students in Education - Hayuningtyas, Arimbi Lolita; Adawiah, Robiatul; Nazah, Safnatun (Jurnal Pendidikan Amartha, 2023)
Pancasila is a formulation and guideline for the life of the nation and state for all Indonesian people. As an Indonesian citizen, implementing the values of Pancasila is mandatory because Pancasila is the basis of the state. The benefits are so that the nation's next generation can apply the values of Pancasila in their daily lives. The purpose of this study is to find out how to apply the values of Pancasila in everyday life. This research uses the literature review method. The results of this study can be concluded that the application of Pancasila values to students is mandatory, because students can take future steps in the lives of society, nation, and state to contribute to the progress of their nation and state.